2014
DOI: 10.1002/app.40668
|View full text |Cite
|
Sign up to set email alerts
|

Foam stability and polymer phase morphology of flexible polyurethane foams synthesized from castor oil

Abstract: Foam stability and segmented polymeric phase morphology of polyurethane foams synthesized partially and completely from castor oil are investigated. Preliminary analysis of the impact of alterations in the polymeric phase on macroscopic stress dissipation in foams is also carried out. The stability and morphology show unique trends depending on the concentration of castor oil used in foam synthesis. While low and intermediate concentrations of castor oil does not significantly affect the foaming process; at hi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
64
0

Year Published

2015
2015
2019
2019

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 56 publications
(65 citation statements)
references
References 39 publications
1
64
0
Order By: Relevance
“…However, both materials show a diffused shoulder like peak at 0.05 Å −1 corresponding to the interdomain spacing of 12.6 nanometers. This result compares well to the reported interdomain separation of scattering domains in polyurethane foams; however, the scattering intensity in this study is very low . This is most likely due to the fact that the NOPs in this study act like cross‐linkers in polyurethane elastomers, which adds to the mixing of the soft and hard segment domains.…”
Section: Resultssupporting
confidence: 88%
See 1 more Smart Citation
“…However, both materials show a diffused shoulder like peak at 0.05 Å −1 corresponding to the interdomain spacing of 12.6 nanometers. This result compares well to the reported interdomain separation of scattering domains in polyurethane foams; however, the scattering intensity in this study is very low . This is most likely due to the fact that the NOPs in this study act like cross‐linkers in polyurethane elastomers, which adds to the mixing of the soft and hard segment domains.…”
Section: Resultssupporting
confidence: 88%
“…Phase images of the elastomers collected via AFM are presented in Figure . The images were collected via tapping mode, and hard domains are represented by lighter colors and softer matrix by darker colors . The elastomer based on M‐60 NOP is composed of the small structures agglomerated into lamella like larger domains.…”
Section: Resultsmentioning
confidence: 99%
“…Elodie et al [33] obtained thermoset polyurethane which based on CO with three different diisocyanates: TDI (toluene diisocyanate), IPDI (isophorone diisocyanate) and HDI (hexamethylene diisocyanate). C. Sharma et al [34] investigated the different weight fraction of castor oil in the hydroxyl component of polyol blend (polyether polyol and castor oil) of petroleum based foam and castor oil based foam. However, there has been little works involving the effect of the castor oil composition content in prepolymer (CO, PEG and MDI) on the properties of the pure castor oil based polyurethane flexible foams.…”
Section: Introductionmentioning
confidence: 99%
“…This provides a hydroxyl value of between 160 and 180 mg KOH g -1 [4,5]. However, this low hydroxyl value along with the presence of secondary hydroxyls results in low functionality and low reactivity [6,7], leading to low crosslinking density, which consequently produces semi-flexible and semi-rigid materials among other limitations [8]. Sharma et al [7] investigated flexible polyurethane foams synthesized partially and completely from castor oil.…”
Section: Introductionmentioning
confidence: 99%
“…However, this low hydroxyl value along with the presence of secondary hydroxyls results in low functionality and low reactivity [6,7], leading to low crosslinking density, which consequently produces semi-flexible and semi-rigid materials among other limitations [8]. Sharma et al [7] investigated flexible polyurethane foams synthesized partially and completely from castor oil. They showed that foams made from 100% of castor oil were unstable and collapsed indicating the inferior reactivity of castor oil with isocyanate.…”
Section: Introductionmentioning
confidence: 99%